Enteral Nutrition Is a Risk Factor for Airway Complications in Subjects Undergoing Noninvasive Ventilation for Acute Respiratory Failure - Kogo, Mariko; Nagata, Kazuma; Morimoto, Takeshi; Ito, Jiro; Sato, Yuki; Teraoka, Shunsuke; Fujimoto, Daichi; Nakagawa, Atsushi; Otsuka, Kojiro; Tomii, Keisuke (Respiratory care, 2017)
Early enteral nutrition is recommended for mechanically ventilated patients in several studies and guidelines. In contrast, the effects of early enteral nutrition on noninvasive ventilation (NIV) have not been investigated extensively. The lack of an established method of airway protection suggests that enteral nutrition administration to these patients could increase airway complications and worsen outcomes. Between January 2007 and January 2015, 150 patients were admitted to our respiratory department for acute respiratory failure and received NIV for >48 h. Of these, 107 subjects incapable of oral intake were retrospectively analyzed. Clinical background and complications were compared in subjects who did and did not receive enteral nutrition. Sixty of the 107 subjects (56%) incapable of oral intake who received NIV also received enteral nutrition. Serum albumin concentration was significantly lower in subjects who received enteral nutrition than in those who did not (mean 2.7 ± 0.68 mg/dL vs 3.0 ± 0.75 mg/dL, = .048). The rate of airway complications was significantly higher (53% [32/60] vs 32% [15/47], = .03), and median NIV duration was significantly longer (16 [interquartile range 7-43] d vs 8 [5-20] d, = .02) in subjects who received enteral nutrition than in those who did not. Multivariate analysis showed that enteral nutrition was unrelated to in-hospital mortality. Among subjects receiving NIV, enteral nutrition was associated with increased risk of airway complications but did not affect mortality. Enteral nutrition should be carefully considered in these patients.